INOVASI ADJUSTABLE FRUIT SLICER UNTUK MENUNJANG EFISIENSI DAN EFEKTIVITAS PROSES PRODUKSI DI UMKM NICE DRY - Pramudya, Henang Duta; Larasati, Aisyah; Afridasari, Mayang Fikri; Santoso, Gilang Aditya; Moekti, M. Rhessal Chandra; Putro, Dilla Praditya Hutomo; Sahal, Ahmad; Khotimah, Khusnul; Putranto, Akhsana Naufal (Universitas Negeri Malang, 2024)
This project purposes to design and develop an innovative fruit cutting tool that can be adjusted by its thickness, which called Adjustable Fruit Slicer. This tool is designed to increase efficiency and effectiveness in cutting fruits. The design process was completed through several stages, including market research, concept development, as well as material analysis and manufacturing. This product is designed to be ergonomic, easy to use, and environmentally friendly with the main material being durable stainless steel. With the advantages of a modern and functional design, Adjustable Fruit Slicer is expected to meet the needs of culinary businesses, especially in fruit processing more efficiently and effectively.